Controversial role of inhibin α-subunit gene in the aetiology of premature ovarian failure - Sundblad, V. (2006)
Background: Premature ovarian failure (POF) is characterized by hypergonadotropic amenorrhoea before the age of 40. Inhibin α-subunit (INHα) gene is proposed as a candidate gene due to its role in negative feedback control of FSH. Methods: Polymorphism -16 C>T of INHα gene was studied in 61 POF patients and 82 controls above 40 years old (C > 40). Substitution 769G>A was studied in 59 POF patients, 76 C > 40 and 73 controls below 40 years old (C < 40). Results: No significant difference in risk of POF development for -16T allele was found when comparing idiopathic POF (I-POF) with C > 40 (Odds ratio = 1.46; 95% confidence interval = 0.63-3.19). Implication of -16C>T polymorphism in serum inhibin levels was analysed in 46 controls, and no significant differences (P > 0.05) were found between CC and CT + TT genotype groups when comparing either mid-follicular phase Pro-αC and inhibin B values or mid-luteal phase Pro-αC and inhibin A values. Heterozygosity for substitution 769G>A was found in 1 of 59 POF woman, 2 of 76 C > 40 and 6 of 73 C < 40. Presence of this su bstitution in a relevant number of control subjects is herein described for the first time. Conclusion: Our results indicate that -16C>T and 769G>A variants in INHα gene may not be associated to POF disease. © 2006 Oxford University Press.